Tuberculosis with Drug-Induced Hepatitis: A Narrative Literature Review - Sari, Riska Yuliana; Zarfiardy Aksa Fauzi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Tuberculosis (TB) is an infectious disease that is a global health problem. The problem is that 5-28% of patients receiving tuberculosis treatment suffer from drug-induced hepatitis on antituberculosis drugs (OAT). The clinical picture should be differentiated from other liver diseases. The level of symptoms varies from asymptomatic to symptomatic, such as nausea, vomiting, abdominal pain, jaundice, hepatomegaly, and increased liver function. OAT use is stopped if clinical symptoms are found and ALT/AST increases ≥3 times, or if there are no symptoms but there is an increase in bilirubin ≥2 mg/dl or ALT/AST values ≥5 times without clinical symptoms. The use of OAT can be continued, but with supervision, if there are no clinical symptoms and the increase in ALT/AST is <2 times and the bilirubin value is <2 mg/dl. Treatment can be carried out again by reintroducing OATs one by one according to ATS recommendations.